Characterization of phenols in salvia elegans and salvia greggii - Pereira, Olívia R. (2014)
Although Salvia elegans and Salvia greggii are commonly used in traditional medicine in North America their main bioactive components remain unknown. The present study aims to identify the main phenolic components of these two plants. Aqueous extracts of both species were prepared according to the procedure described by Ferreira et al and the total phenolic content of the extracts was evaluated through an adaptation of the Folin-Ciocalteu method. Identification of the phenolic compounds was accomplished by reversed-phase HPLC with DAD and ESI-MSn analysis in negative mode. The aqueous extracts of S. elegans and S. greggii contained 201±46 and 136±1 μg GAE/mg of extract, respectively. The two extracts were mainly composed of rosmarinic acid, which is typically found in Salvia plants. S. elegans also contained significant amounts of other caffeic acid derivatives, in particular lithospermic acid and luteolin derivatives. S. greggii extract, contain also luteolin and apigenin derivatives. The main phenolic constituents of S. elegans and S. greggii are here described for the first time. This knowledge may help further understanding of the claimed health-benefits for these two plants.